2015
DOI: 10.1002/ase.1534
|View full text |Cite
|
Sign up to set email alerts
|

Peer mentoring program in an interprofessional and interdisciplinary curriculum in Brazil

Abstract: The Federal University of São Paulo, Baixada Santista Campus was founded in 2006 with five degree-granting programs in physical education, physiotherapy, nutrition, psychology, and occupational therapy. The guiding principle behind the programs' educational mission was centered on the development of health care professionals capable of working in interdisciplinary teams with an emphasis on holistic patient care. This pedagogical structure required peer-mentoring programs in order to integrate different areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
(58 reference statements)
1
21
0
Order By: Relevance
“…Attendance at the near‐peer teaching program was 59% ( n = 23), which is similar to a result found by de Oliveira et al (). These authors found that 57% of students participated in at least one academic activity related to a peer‐mentoring program.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Attendance at the near‐peer teaching program was 59% ( n = 23), which is similar to a result found by de Oliveira et al (). These authors found that 57% of students participated in at least one academic activity related to a peer‐mentoring program.…”
Section: Discussionsupporting
confidence: 89%
“…The best academic performance found in the current study can be compared with results from previous studies. Again, de Oliveira et al () conducted a study to evaluate the effectiveness of a peer‐mentoring program in histophysiology and gross anatomy in an interdisciplinary and interprofessional curriculum at Federal University of São Paulo (UNIFESP, Brazil). The authors found that students who participated in peer‐mentoring activities in at least one session of the two areas of mentoring (histophysiology and anatomy) had better academic performance than those who did not participate or who participated in only one area.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching in near‐peer programmes encourages those working in clinical practice to refresh their own knowledge and keep up to date . Across the spectrum of health care roles, there is a growing expectation that professionals will engage in teaching and training others . In order to create a skilled clinical teaching workforce it would seem prudent to provide teaching opportunities from an early career stage, and near‐peer programmes do exactly this.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
“…There is evidence from Brazil for improved examination scores in undergraduate students of sport and exercise science attending a near‐peer teaching course . Another Brazilian study has evaluated near‐peer teaching between undergraduates in various allied health care professions and supports improved academic success …”
Section: The Evidence Behind Near‐peer Teachingmentioning
confidence: 99%
“…4,[6][7][8] In one study, dental hygiene students from underrepresented racial and ethnic groups (UREG) perceived the lack of UREG faculty members in the program as an additional barrier to successful completion of their education. 3,6,[10][11][12] In other studies, the availability of faculty, faculty support, and continuous feedback were reported to increase retention in educational programs. 3,6,[10][11][12] In other studies, the availability of faculty, faculty support, and continuous feedback were reported to increase retention in educational programs.…”
mentioning
confidence: 99%